Illegal drugs in Lima and Callao high schools: family factors associated with the consumption - Gutiérrez, César (2009)
Introduction: Drug abuse is a public health problem worldwide and has increased in developing countries. Illegal drugs such as marihuana and inhalants (terokal, PVC, benzene and/or acetone) are consumed increasingly at younger ages. Objectives: To determine the epidemiology, personal, scholastic and familial factors (parental involvement with their children's activities) associated to marihuana and inhalants use by high school students in Metropolitan Lima and Callao. Design: Analytical and transversal study. Setting: Metropolitan Lima and Callao. Participants: Five thousand six hundred and forty-seven high school 2nd, 4th and 5th year students. Interventions: Review and analysis of the "Prevention and drug use by high school students” national study database conducted by the National Commission for Development and Life without Drugs 2005. Results: Lifetime prevalence of illicit drug use among secondary school students in Metropolitan Lima and Callao was 5,9% (marihuana) and 4,8% (inhalants). Marihuana use was more common in men (7,6%) than in women (2,71%), p <0,001. Marihuana and inhalants were used significantly more frequently (p <0,001) by those who did not live with their parents, had had two or more school failures, having behavior problems in school and those ‘playing hookey‘ (truancy). The type of school (public or private) was not significantly associated with history of either marihuana or inhalants. Risk factors found for marihuana and inhalants were having some behavioral or discipline problems during their studies, two or more antecedents of school failure and ‘playing hookey’. Among family involvement protective factors we found: parental knowledge on child location after classes or on weekends, parental control on television watching, parents eating with the child 4 to 7 days a week, and the teenager informing his parents where he went in evenings or weekends. Conclusions: Frequency of drug abuse increased among children with history of school failure and indiscipline and family dysfunction. Family involvement in children's activities represents a protective factor against drug abuse; the family has an extremely significant role in shaping the adolescent.